Peran Organisasi Masyarakat Sipil Dalam Penciptaan Keserasian Sosial - Ratih Probosiwi (Jurnal Penelitian Kesejahteraan Sosial, 2018)
In every government program implementation, it needs support from three government pillars namely the government itself, the private sector and civil society. Civil society organizations or better known as CSOs have a role in the history of Indonesian government. The implementation of the social harmony program as one of the government programs to prevent and create harmony and harmonization of the community also needs to be supported by CSOs with all their roles. This study aims to examine the role of CSOs in creating social harmony through the social harmony program launched by the Ministry of Social Affairs. Data is obtained through literature testing, in-depth interviews, as well as field tests or observations. The results of the study show that CSOs still have very little role in implementing social harmony programs. The social harmony forum as the main implementer of the program lacked a portion of involvement in civil society and its organizations to participate in the implementation of the program. An understanding must be given to program implementers to involve CSOs in building harmony and harmony between communities.Â Keywords:Civil Society Organization; Involvement; Impementation; and Social Harmony